A city that never existed: Xiao Bai’s literary remaking of 1931 Shanghai - Magagnin, Paolo (Journal of Architecture and Urbanism, 2017)
This article provides an account of the literary recreation of the semi-colonial Shanghai of 1931, carried out by the Chinese contemporary author Xiao Bai in his 2011 novel Zujie. It also includes the features and implications of such an operation. Critically praised as a turning point in contemporary Chinese fiction about old Shanghai, the novel appears to transcend genre categories, and was welcomed as a heterogeneous “third type” crossing the boundaries between genre fiction and pure literature. Inspired by historical facts and supported by painstaking archival research, Zujie originally incorporates a variety of literary models, narrative techniques, sources, genres, themes, and perspectives. The heterogeneity at play in the novel can be essentially scrutinised at three levels. Such levels are: the debate on the genre as it emerges from a number of paratextual sources; the treatment of historical factuality and its relationship with fictional creation; the use of polyphonic devices, with reference to the portrayal of hybrid characters, deliberately disorienting narrative techniques, and a re-elaboration of imported and domestic sources and literary models that plays havoc with the very notions of foreignness and identity. Xiao Bai’s original representation of 1930s Shanghai is analysed and commented upon with respect to such factors. Finally, the significance of this multi-layered literary operation and its implications for the reader are highlighted.